The Effectiveness of a Pre-Exercise Performance Drink (PRX) on Indices of Maximal Cardiorespiratory Fitness - Greenwood Lori; Greenwood Mike; Byars Allyn; Simpson Warren K (Taylor & Francis Group, 2006)
Abstract This study examined the effectiveness of a pre-exercise drink (PRX) called EM·PACT on indices of maximal cardiorespiratory fitness. Twenty-four males (n = 12) and females (n = 12) ages 18-24 years (20.25 + 1.42), volunteered as subjects. Each subject performed two randomized trials of a VO2max treadmill test within a week of each other. Subjects in this randomized, placebo controlled, counter balanced, crossover design, ingested either a placebo (water) or PRX 20 minutes before each exercise bout. VO2max and time to exhaustion (Time) during graded exercise testing were evaluated. Using paired samples t-tests, significantly greater mean values were found in VO2max and Time for the PRX trial compared to the placebo trial (p < .05). Results indicate that indices of cardiorespiratory fitness; specifically VO2max and Time are enhanced by ingestion of PRX prior to exercise testing. The combined results of this investigation may provide meaningful practical applications for coaches and athletes alike regarding ergogenic hydration options.